Mechanical properties of bemban fibres composites - Norhayati, Yahaya. (Universiti Malaysia Sarawak, UNIMAS, 2004)
Be m b an ( Donax Grandis ) bast fibre, natural fibre was combined with polyester resin m a trix to produce fibre com posites. The co m p osites were fabricated using continuous reinforcing fibres, 0 and 90-degree properties. These are to evaluate the effect of lay-up sequence on the m echanical prop erties of the composites. A tensile tes t has been ca rrie d out and all the specim ens were cond itioned acco rding to AST M D3039 before carry o u t the test. This research and experim e ntal work ar e done in order to eval uate the potential of natural fibre that can be found in Sarawak, which are bem b an.